Restorative Justice dalam Perkara Kekerasan terhadap Anak di Kejaksaan Negeri Purbalingga - Fera Eliza; Andika Kusumawardani; Dianing Sekar Mayang; Silvi Sakinatunnisa (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Laws are fundamentally created to provide justice for the entire society. Law enforcement can be carried out through litigation and non-litigation processes. The government is currently striving for non-litigation law enforcement through Restorative Justice. This article aims to explain the process by which a prosecutor convinces the victim to pursue Restorative Justice enforcement and the importance of the presence of village officials in Restorative Justice efforts. The data is based on interview methods and document analysis, analyzed descriptively. The research results indicate that, fundamentally, prosecutors do not convince the victim to undergo Restorative Justice. Instead, prosecutors act as facilitators suggesting that there is an alternative way to resolve non-litigation cases through Restorative Justice. The urgency of the presence of village officials as community figures in the Restorative Justice process is a requirement of Restorative Justice. Currently, the government is attempting to maximize the resolution of cases through non-litigation means, which is highly relevant in cases related to violence against children, especially in the efforts to implement Restorative Justice in cases of violence against children in the Public Prosecutor's Office of Purbalingga under the name Suspect Saeful Trianto alias Amir Bin Hadigun. The application of Restorative Justice requires the participation and awareness of the parties involved to be implemented to the fullest extent.Keyword: Justice, Law, Non-litigation law enforcement, Restorative Justice, Violence against children